2014
DOI: 10.1111/ajt.12906
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Well-Being of Living Kidney Donors: Findings From the RELIVE Study

Abstract: Following kidney donation, short-term quality of life outcomes compare favorably to US normative data but long-term effects on mood are not known. In the Renal and Lung Living Donors Evaluation Study (RELIVE), records from donations performed 1963–2005 were reviewed for depression and antidepressant use pre-donation. Post-donation, in a cross-sectional cohort design 2010–2012, donors completed the Patient Health Questionnaire (PHQ-9) depression screening instrument, the Life Orientation Test-Revised, 36-Item S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 34 publications
3
53
0
1
Order By: Relevance
“…One percent reported that kidney donation affected their health in a negative way. Predictors of depression post-kidney donation included, non-white race, younger age, longer recovery post-donation, greater financial burden and feelings of moral obligation (11). …”
Section: Living Donor Transplantationmentioning
confidence: 99%
See 4 more Smart Citations
“…One percent reported that kidney donation affected their health in a negative way. Predictors of depression post-kidney donation included, non-white race, younger age, longer recovery post-donation, greater financial burden and feelings of moral obligation (11). …”
Section: Living Donor Transplantationmentioning
confidence: 99%
“…Since a large percentage of ILDA’s also perform the psychosocial evaluation, it has recently been recommended that the documentation for the psychosocial evaluation is separate from the ILDA evaluation (11). The documentation of psychosocial evaluation should be included in the potential donor’s medical record.…”
Section: The Psychosocial Evaluation Of Living Donorsmentioning
confidence: 99%
See 3 more Smart Citations